Writing research papers : a guide to the process - Weidenborner, Stephen; Caruso, Domenick; Parks, Gary ([S.l.] : Bedford/St. Martin's, 2004)
A friendly, easy-to-use guide, Writing Research Papers walks students through every step of the research process $1 (Bfrom finding a topic to searching the Web to formatting the final manuscript. The seventh edition is thoroughly revised to help students find and evaluate the very best sources amidst the flood of information that electronic searching makes availables